Macintyre, Alasdair : animales racionales y dependientes. Barcelona. Paidós Básica, 2001 - Casiva Gaitán, María Isabel (2004)
Fil: Casiva Gaitán, María Isabel. Pontificia Universidad Católica Argentina; Argentina